Impact of Collateral Circulation on Early Outcome and Risk of Hemorrhagic Complications after Systemic Thrombolysis. Issue 8 (December 2014) - Brunner, Freimuth; Tomandl, Bernd; Hanken, Katrin; Hildebrandt, Helmut; Kastrup, Andreas
Background: In stroke patients, collateral flow can rapidly be assessed on computed tomography angiography (CTA). Aims: In this study, the impact of baseline collaterals on early outcome and risk of symptomatic intracerebral hemorrhages after systemic thrombolysis in patients with proximal arterial occlusions within the anterior circulation were analyzed. Methods: Collateralization scores were determined on the CT angiography source images (0 = absent; 1 ≤ 50%, 2 > 50% but <100%, and 3 = 100% collateral filling) of patients with distal intracranial carotid artery and/or M1 segment occlusions treated from 2008 to December 2011. A collateral score of 0 to 1 was designated as poor and 2 to 3 as good collateral vessel status. Outcome variables included in hospital mortality, favorable outcome at discharge (modified Rankin score ≤ 2), and rates of symptomatic intracerebral hemorrhage based on the European–Australasian Acute Stroke Study II definition. Results: Among 246 subjects (mean age of 74 years; median National Institutes of Health Stroke Scale N at admission 14), 205 patients (83%) had good collaterals, whereas 41 patients (17%) had poor collaterals, respectively. Patients with poor collaterals had significantly higher rates of in-hospital mortality (41% vs. 12%, P < 0·001), of symptomatic intracerebral hemorrhage (15% vs. 4·9%, P < 0·05) and had significantly lower rates of favorable early clinical outcome (0% vs. 28%, P < 0·001) compared with those with good collaterals. The grade of collateralization was independently associated with in-hospital mortality ( P < 0·001), early clinical outcome ( P < 0·01), and rates of symptomatic intracerebral hemorrhage ( P < 0·01). Conclusion: Patients with proximal arterial occlusions within the anterior circulation and poor baseline collaterals have a poor early functional outcome and high rates of symptomatic intracerebral hemorrhage after systemic thrombolysis. Since similar findings have also been reported after endovascular therapy, strategies to improve collateral blood flow should be assessed in this patient population.